War Crimes Trials and Enacting the Social in Society, or How Forrest Gump Became an Honorary Citizen of the Former Yugoslav States - Kardov, Kruno (2006)
Author analyses the relationship between criminal trials at ICCs and reconciliation of local communities. Various empirical studies (e.g. Stover&Weinstein 2004) have showed there is no direct link between criminal trials (international, national, and local/traditional) and reconciliation. The author's central thesis is based on following arguments: 1. juridical processes based on dichotomies (guilt/innocence, criminal/victim, etc.) create a gap between the perpetrator and the victim which is rationally created and proves to be unstable at the level of everyday life of post-war communities ; 2. rationally created arguments and external efforts in reconstructing community necessarily destroy previous knowledge structures and bring into question moral order of community. Since the law is always on the side of multiple Other the social reconciliation based only on trials produces a society whose exemplary member suffers from a Forrest Gump syndrome. Gump embodies all the contradictory stories and different historical narratives present within a society and the price paid for such mechanical unity is absence of profound social values. Disembedded and released from all cultural boundaries, Forrest Gump is constantly running. At the end, running becomes his structural condition.